1991
DOI: 10.1002/ijc.2910480206
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptors in endocrine‐therapy‐resistant human prostate cancer

Abstract: Despite the initial androgen-dependent growth of most human prostate cancers, eventually all prostate cancers become androgen-independent at varying intervals after androgen ablation or anti-androgen therapy. In order to gain more insight into the role of the androgen receptor (AR) in this process, AR and prostate-specific antigen (PA) expression was evaluated immunohistochemically in prostatic tumour tissues from patients who developed urinary flow obstruction between 4 and 107 months after onset of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
180
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(188 citation statements)
references
References 20 publications
8
180
0
Order By: Relevance
“…The most important finding was the proof that the AR is expressed not only in primary prostate tumors 4,5 but also in their corresponding metastatic lesions, as shown in vivo in immunohistochemical studies. 6,7 It has become clear that progression from androgen-dependent to androgen-independent prostate tumor growth is not associated with loss of the AR.…”
mentioning
confidence: 88%
“…The most important finding was the proof that the AR is expressed not only in primary prostate tumors 4,5 but also in their corresponding metastatic lesions, as shown in vivo in immunohistochemical studies. 6,7 It has become clear that progression from androgen-dependent to androgen-independent prostate tumor growth is not associated with loss of the AR.…”
mentioning
confidence: 88%
“…Recent evidence also androgen-independent disease. However, it is now known that the majority of metastatic deposits of prostate cancer continue to express androgen receptor (54)(55)(56), and current theories of androgen independence have focussed on the presence of a functioning androgen receptor (i.e. AR hypersensitivity, promiscuity, amplification etc.)…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Immunohistochemical staining of tumor biopsies showed that the AR is expressed in most prostate cancers, often at higher levels in relapsed tumors than in primary tumors. 5,6 AR gene amplification has been reported in up to 30% of recurrent tumors. [7][8][9] How AR upregulation might confer a growth advantage under androgen ablation conditions is still not fully understood.…”
mentioning
confidence: 99%